Monitoring the morphology development of polymer‐monolithic stationary phases by thermal analysis. Issue 1 (22nd November 2013) - Wouters, Sam; Wouters, Bert; Vaast, Axel; Terryn, Herman; Van Assche, Guy; Eeltink, Sebastiaan
<x xml:space="preserve">Abstract</x> Thermal analysis and SEM were employed to gain insights in the different stages of morphology development and the thermal properties of polymer‐monolithic stationary phases. The studied system was a thermally initiated free‐radical copolymerization reaction at 70°C of styrene and divinylbenzene in the presence of tetrahydrofuran and 1‐decanol. The key events in the early stages of morphology development are initiation, chain growth, branching, and cyclization, leading to microgel particles. Interparticle reactions through pendant vinyl groups lead to the formation of microgel clusters. The rapid increase in molecular weight and cross‐link density of the microgel clusters causes a reaction‐induced phase separation, and the formation of a macroscopic network of interconnected globules was observed (macrogelation) at around 45 min. After 3 h or 65% conversion, a space‐filling macroporous monolithic network was observed. Afterwards, mainly growth of existing globules takes place, reducing the macropore size. The porogen ratio affects the timing of the reaction‐induced phase separation, strongly influencing the morphology of the polymer material. The use of a mixture of divinylbenzene isomers yielded a monolithic material that is less cross‐linked at the surface compared to the central part of the polymer backbone due to copolymerization‐composition drift. The less cross‐linked outer layer starts devitrifying at 100°C.